Clinical, endocrinal and radiological profile of cases with polycystic ovary syndrome in tertiary care centre - Raviraj Khairnar; Archana Khairnar (New Indian Journal of OBGYN, 2023)
Background: Polycystic ovary syndrome (PCOS) is a chain of pathological, biochemical and endocrinal events which usually present with complaints like infertility, features of hyperandrogenemia (HA), amenorrhea and signs of metabolic disturbances like impaired glucose tolerance. Aim: To assess clinical, endocrinal and radiological profile of cases with polycystic ovary syndrome in tertiary care centre. Methodology: Descriptive cross-sectional study conducted in gynaecological OPD on 100 women having PCOS diagnosed by Rotterdam criteria. Results: Most of cases were belongs to age group of 20 to 24 years (47%) with mean age of patients was 23.69 ± 4.48 years. Half were obese (48%). Almost 50% women showed features of hyperandrogenism and 86% had oligomenorrhea. Serum testosterone levels were found to be increased among 54% women. Out of three Rotterdam criteria for diagnosis of PCOS, most cases had chronic anovulation (irregular cycles) followed by 83% had USG suggestive of PCOS and 46% had hyperandrogenism. Association between hyperandrogenism, acanthosis nigricans and obesity were statistically significant (p<0.05). Out of 100 cases, 83% cases had feature suggestive of PCOS on USG. Conclusion: Complaint of any feature of PCOS should not be neglected because timely therapeutic intervention can halt the process of development of PCOS. PCOS is symptoms complex which is not clearly defined, so it needs proper monitoring. Awareness regarding various symptoms and role of weight reduction in treatment of PCOS should be spread.